(untitled) (TAJ: Journal of Teachers Association, 2018)
Background: Perforated or gangrenous appendicitis in patient with a lately presented acute appendicitis remains a challenge for practicing surgeons and continues to be associated with more deadly complications. Results might improve with earlier consideration of the diagnosis followed by prompt surgical intervention. Objective: To identify the risk factors of appendiceal perforation, gangrene and other sequelae in patients with delayed presentation of acute appendicitis and its effects on the prognosis. Patients and Methods: This cross-sectional study was carried out from January, 2015 to July, 2017 (2½ years) in Rajshahi medical college hospital and also it’s neighboring several private hospitals. Those patients of both genders between 12 years to 65 years old, admitted during that period with signs and symptoms of acute appendicitis for more than 48 hours but otherwise healthy (i.e. not having any other comorbidities) were subjected to the present study. The parameters of our study were incidence of appendiceal perforation or gangrene, peri-appendiceal abscess formation, generalized peritonitis, length of hospital stay and post-operative complications. Results: During the study period, a total of 73 patients underwent appendicectomies and 23 patients were excluded, leaving 50 who met the inclusion criteria, 23 males (46%) and 27 females (54%). Of all the risk factors studied, the patient’s pre-hospital time delay was the most important risk factor for perforation (43 patients i.e. 86%) and there were little number of patients with the in-hospital delay (7 patients i.e. 14%). The reasons behind this pre-hospital as well as in-hospital delay were multifactorial. Overall appendiceal perforation occurred in 22 (44%) patients, patients presented with gangrenous appendicitis were 14 (28%), periappendiceal abscess formation was found in 9 (18%) patients, and patients presented with generalized peritonitis were 5 (10%). The duration of hospital stay ranged from several days to several weeks. Post-operative complications occurred in 40 (80%) cases. Post-operative complications were monitored and addressed as: prolonged ileus, wound sepsis as major and minor wound infection, intra-abdominal sepsis as pelvic abscess and faecal fistula. Conclusion: As the time course increases from the initiation of the first symptoms to the definitive management, the complication rate increases and acutely inflamed appendicitis gradually converts to more lethal forms. TAJ 2017; 30(1): 42-48